2022
DOI: 10.1093/carcin/bgac055
|View full text |Cite
|
Sign up to set email alerts
|

MPZL1 upregulation promotes tumor metastasis and correlates with unfavorable prognosis in non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC), accounting for 85% of all lung cancer, is one of the leading causes of cancer-related death worldwide. Previously, we demonstrated that MPZL1 gene amplification promotes liver cancer metastasis through activating Src/Cortactin pathway. However, the clinical relevance and biological roles of the MPZL1 gene in lung cancer are still unknown. Here, we found that MPZL1 expression upregulates in human NSCLC, which is partly due to the copy number amplification of this gene. Next, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…We further verified the effect of COL11A1 on the prognosis of LUAD patients using the GSE72094 and Kaplan-Meier plotter databases and confirmed that the prognosis of LUAD patients with high expression of COL11A1 was poor. Feng et al demonstrated that COL11A1 is a potential effector gene that is positively regulated by MPZL1 and correlates with poor prognosis in LUAD patients [ 24 ]. Therefore, COL11A1 may be a potential prognostic biomarker in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…We further verified the effect of COL11A1 on the prognosis of LUAD patients using the GSE72094 and Kaplan-Meier plotter databases and confirmed that the prognosis of LUAD patients with high expression of COL11A1 was poor. Feng et al demonstrated that COL11A1 is a potential effector gene that is positively regulated by MPZL1 and correlates with poor prognosis in LUAD patients [ 24 ]. Therefore, COL11A1 may be a potential prognostic biomarker in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also conducted an analysis of DGE with the aim of identifying the transcriptomic signature of CVID in GC samples. An enrichment was observed in pathways involved in the innate immune response against pathogen-associated molecular patterns and type 2 immune responses to parasites and protozoa in the distal small intestine and to viruses ( TAS1R3 and SYT1 , respectively) 51 , 52 , 53 , 54 ; DNA repair ( E2F7 ) 55 ; cell proliferation, migration, and invasion in several types of cancers ( MPZL1 ) 56 , 57 , 58 ; and regulation of cell cycle, inflammation, and host-defense response ( PGRN ). 59 , 60 , 61 …”
Section: Discussionmentioning
confidence: 99%
“…UHRF1 is overexpressed in T-cell ALL and its knockdown reduces c-MYC expression and viability in these malignancies 33 . Other genes hypomethylated and overexpressed in PTCL -RAB13, MPZL1, CDK14 -were implicated in tumor progression of several different tumors including B-cell lymphomas, and glioblastomas, lung and ovarian 34,35,46,47 . Among genes, we detected to be hypermethylated and silenced in PTCL are major tumor suppressors, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes from this group, such as UHRF1, MPZL1, CDK14, RACGAP1, RAB13, and others have oncogenic functions in various solid tumors, leukemias, and lymphomas either predicting poor prognosis, involved in tumor migration, metastasis, or maintenance [31][32][33][34][35] .…”
Section: Deregulated Promoter Methylation Is Associated With Changes ...mentioning
confidence: 99%